Lassa fever outbreak in adolescents in North Central Nigeria: report of cases - H.O. Akhiwu; E.S. Yiltok; A.O. Ebonyi; S. Gomerep; N.Y. Shehu; E.P. Amaechi; A.E. Onukak; P. Iduh; A.A. Oyagbemi; G. Omame; P.M. Ashir; D.Z. Egah; et al. (Journal of Virus Eradication, 2018)
Background: Lassa fever (LF) is a viral haemorrhagic fever endemic to West Africa. The clinical presentation and course is variable, making diagnosis difficult. Aim: To report the outbreak and identify the common clinical presentations of LF in paediatric patients in Jos, Plateau State, North Central, Nigeria. Methods: This was a retrospective review of patients managed for LF during the June–August 2017 outbreak. LF was suspected in cases with: fever of less than 3 weeks’ duration that had not responded to antimalarials or antibiotics, myalgia, abdominal pain, prostration and history of contact with any person diagnosed with LF. LF was confirmed by a positive reverse transcriptase polymerase chain reaction test (RT-PCR). Results: Ten adolescents were studied. The common presenting complaints were fever (100%), prostration (90%) and headache (70%) while the commonest clinical signs were pyrexia (temperature >38.0oC; 90%), prostration (80%) and abdominal tenderness (80%). Leukocytes were present in urine in 60%. Eight individuals recovered fully, one adolescent died and one developed intestinal perforation necessitating laparotomy. Conclusion: In settings such as North Central Nigeria, LF should be suspected in any patient with fever that is unresponsive to antimalarials and antibiotics, especially in the presence of prostration, tachypnoea, tachycardia or abdominal tenderness. Early diagnosis and treatment is needed to reduce mortality from the disease and protect against transmission to health personnel.